Natural-product-based, carrier-free, noncovalent nanoparticles for tumor chemo-photodynamic combination therapy - Zhonglei Wang; Liyan Yang (Elsevier, 2024)
Cancer, with its diversity, heterogeneity, and complexity, is a significant contributor to global morbidity, disability, and mortality, highlighting the necessity for transformative treatment approaches. Photodynamic therapy (PDT) has aroused continuous interest as a viable alternative to conventional cancer treatments that encounter drug resistance. Nanotechnology has brought new advances in medicine and has shown great potential in drug delivery and cancer treatment. For precise and efficient therapeutic utilization of such a tumor therapeutic approach with high spatiotemporal selectivity and minimal invasiveness, the carrier-free noncovalent nanoparticles (NPs) based on chemo-photodynamic combination therapy is essential. Utilizing natural products as the foundation for nanodrug development offers unparalleled advantages, including exceptional pharmacological activity, easy functionalization/modification, and well biocompatibility. The natural-product-based, carrier-free, noncovalent NPs revealed excellent synergistic anticancer activity in comparison with free photosensitizers and free bioactive natural products, representing an alternative and favorable combination therapeutic avenue to improve therapeutic efficacy. Herein, a comprehensive summary of current strategies and representative application examples of carrier-free noncovalent NPs in the past decade based on natural products (such as paclitaxel, 10-hydroxycamptothecin, doxorubicin, etoposide, combretastatin A4, epigallocatechin gallate, and curcumin) for tumor chemo-photodynamic combination therapy. We highlight the insightful design and synthesis of the smart carrier-free NPs that aim to enhance PDT efficacy. Meanwhile, we discuss the future challenges and potential opportunities associated with these NPs to provide new enlightenment, spur innovative ideas, and facilitate PDT-mediated clinical transformation.